Prevalence and correlates of sexual harassment in professional service firms - Hardies, Kris (Frontiers in Public Health, 2023)
Background: Despite their significance, limited research has been conducted on sexual harassment in professional service firms (PSFs). Methods: I gathered survey data from 321 Belgian employees (155 women, 166 men) of global accounting and law firms. I report on the prevalence of sexual harassment in PSFs based on traditional sexual harassment items and not-man-enough harassment items. I also examine correlations of respondents’ experiences with workplace sexual harassment with perceived acceptance of sexual harassment by one’s peers (social norms), personality traits, and demographic and job-related factors. Results: Experiences of workplace sexual harassment were widespread in the current sample: 88.5% of women and 83.3% of men experienced at least once or twice some form of sexual harassment at work during the past 24 months. The most frequent types of sexual harassment reported are examples of (verbal) forms of gender harassment. Instances of traditional harassment were experienced equally often by men and women, while not-man-enough harassment was much more frequently experienced by women. Severe physical sexual harassment was less frequent. Workplace sexual harassment is positively correlated with perceived acceptance of sexual harassment by one's peers and negatively with job level. Conclusions: Results of the current study align with research that links workplace sexual harassment with workplace culture and suggest that both men and women in PSFs experience enforcement of gender roles). It seems quintessential for firms to create working environments and cultures in which sexual harassment is clearly and unambiguously condemned and sanctioned.